2019
DOI: 10.3390/economies7020037
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Agricultural Productivity and Its Components in Bangladeshi Regions (1987–2009): An Application of Bootstrapped Data Envelopment Analysis (DEA)

Abstract: The present study applies a bootstrapped data envelopment analysis (DEA) procedure to compute bias-corrected measures of agricultural total factor productivity (TFP) change and its components (technical change and technical efficiency change) using a panel data of 19 regions of Bangladesh covering a 23-year period (1987–2009), thereby overcoming the limitation of the lack of statistical inference of the conventional non-parametric DEA. Results revealed that overall productivity grew at a modest rate of 0.03%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…By 2019, Bangladesh ranked 4th in the world in rice production ( FAO, 2019 ) and was making significant improvements in producing vegetables, fish, livestock and poultry ( FAO, 2017 ). These improvements were due to investment in agricultural policy and infrastructure such as the introduction of High Yielding Varieties (HYV) of rice, use of modern inputs including chemical fertilizers, pesticides, irrigation, storage systems, use of subsidies, micro-credit supports and marketing capacity ( Gautam and Faruqee, 2016 ; Bagchi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…By 2019, Bangladesh ranked 4th in the world in rice production ( FAO, 2019 ) and was making significant improvements in producing vegetables, fish, livestock and poultry ( FAO, 2017 ). These improvements were due to investment in agricultural policy and infrastructure such as the introduction of High Yielding Varieties (HYV) of rice, use of modern inputs including chemical fertilizers, pesticides, irrigation, storage systems, use of subsidies, micro-credit supports and marketing capacity ( Gautam and Faruqee, 2016 ; Bagchi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Efficient water management in agriculture has been extensively analysed in recent research, with the results of those studies driving progress by identifying the most appropriate policies for each situation (Wang et al 2018;Bagchi et al 2019;Berbel et al 2019;Geng 2020;Martinho 2020). The empirical analysis carried out in this research yields new findings that can better guide the actions of irrigators and policy-makers.…”
Section: Introductionmentioning
confidence: 95%
“…Depending on whether an input-or output-oriented model is used, DEA determines the extent to which the inputs could be reduced while maintaining the same output levels, or vice versa (Charnes et al 1978). The scientific literature includes numerous studies that demonstrate its capacity for measuring efficiency in different spheres, such as financial performance (Sukmana et al 2020;Hafsal et al 2020), industrial production (Guo et al 2020;Rezaee et al 2020), agrarian production (Li et al 2018Bagchi et al 2019), and even services (Yin et al 2020;Cinaroglu 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that efficient regions had higher level of land, labor, energy and capital productivity and productivity of contract work than less efficient regions. Another interesting application of DEA on regional level is presented by group of authors (Bagchi et al, 2019). They analyzed growth in agricultural productivity in 19 Bangladeshi regions for 23 years period using a bootstrapped DEA procedure.…”
Section: Introductionmentioning
confidence: 99%